Expression and clinical significance of NCOA5 in epithelial ovarian cancer - Song, Xiaoping; Qian, Da; Dai, Ping; Li, Qian; Xi, Qiuping; Sun, Kailv (Frontiers in Oncology, 2023)
Background: Nuclear receptor coactivator 5 (NCOA5) plays a significant role in the progression of human cancer. However, its expression in epithelial ovarian cancer (EOC) is unknown. The current study was designed to explore to investigate the clinical significance of NCOA5 and its correlation with the prognosis of EOC. Methods: Immunohistochemistry was used to detect the expression of NCOA5 in 60 patients with EOC and statistical analysis was performed to assess its relevance to clinicopathologic features and survival. Results: NCOA5 expression was significantly higher in EOC than in normal ovarian tissues (P < 0.001). Its expression level was significantly correlated with FIGO stage (P <0. 05) and subtypes of ovarian cancer (P < 0.001), while not correlation with age 、differentiation and lymph node metastasis (P>0.05). Correlation analysis showed that NCOA5 was significantly correlated with CA125 (P < 0.001) and HE4 (P < 0.01). In a Kaplan-Meier analysis of overall survival rates, the patients with low expression of NCOA5 had significantly longer survival than high expression of NCOA5 (p=0.038). Conclusion: NCOA5 high expression is associated with EOC progression and can be an independent factor affecting the prognosis of EOC patients.